Prophylactic mirtazapine and ondansetron for the prevention of post spinal anesthesia shivering in lower abdominal surgeries: a randomized clinical study - Mopi, Tailyang; Eshori, Longjam; M., Dhayanithy; K., Vigneshwaravibhava; Deb, Rohan (International Journal of Research in Medical Sciences, 2025)
Background: Spinal anesthesia is a frequently employed method for administering anesthesia during lower abdominal surgeries and is considered a safe anesthetic approach utilized for both elective and emergency operations. However, potential complications can arise, including hypotension, post-dural puncture headache (PDPH), and shivering. Objective was to evaluate the efficacy of prophylactic mirtazapine and ondansetron in the prevention of post spinal anaesthesia shivering (PSAS) among the patients who underwent lower abdominal surgeries. Methods: The study groups were divided into two, named group M and group O. The total sample size was 88 (44 patients in each group). Patients in group M received mirtazapine 30 mg tablet (Mirtakem 30) with sips of water and group O received ondansetron 4 mg tablet (Ondem 4) with sips of water. Results: The incidence of PSAS among the patients in mirtazapine and ondansetron groups were 45.5% and 81.8%. PSAS was significantly higher among the patients in the ondansetron group when compared to the mirtazapine group (p<0.001). The time of onset of shivering was delayed for the patients in the ondansetron group when compared to the patients in the mirtazapine group, but it was not found to be statistically significant. Conclusions: It could be safely concluded that prophylactic administration of mirtazapine attenuate shivering with minimal hazards in patients scheduled for lower abdominal surgery under spinal anesthesia when compared to ondansetron.